The effect of competence and participation on accountability in village fund management with information technology as a moderating variable - Yohanes Suhardjo; Faisal Faisal (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
Accountability in village fund management remains a critical challenge in Indonesia, where issues such as mismanagement and lack of transparency persist. This study aims to explore the impact of competence, community participation, and the use of information technology on the accountability of village fund management, particularly examining whether information technology moderates these relationships. The research population includes village officials, the village consultative committee, and district apparatus in Karangawen District, Demak Regency. Using purposive sampling, 108 respondents were selected to provide primary data, which were analyzed using the Partial Least Squares (PLS) method.The results show that competence and community participation significantly influence the accountability of village fund management. Competence improves decision-making and administrative transparency, while participation plays the most significant role by fostering accountability through inclusive planning and evaluation processes. Although the use of information technology positively affects accountability by enhancing transparency and accuracy in reporting, it does not act as a moderating variable in the relationship between competence or participation and accountability. This finding highlights the need for improved infrastructure, training, and tailored technological solutions for rural settings.The practical implications of this study include the importance of enhancing training programs to improve the competence of village officials, encouraging community participation through effective socialization, and optimizing the use of information technology. By addressing these factors, this research contributes to strengthening village fund governance and preventing irregularities in fund management in Indonesia.